Development and validation of the health literacy environment scale for Chinese hospitals from patients’ perspective - Tong, Yingge; Wu, Yixue; Han, Zhiqing; Xue, Zihao; Wei, Yeling; Lai, Shanyuan; Chen, Ziyi; Wang, Miaoling; Chen, Siyi (Frontiers in Public Health, 2023)
Introduction While the research on improving individual health literacy by promoting individual skills and abilities is increasing, less attention has been paid to the complexities of the healthcare environment that may influence patients’ ability to access, understand, and apply health information and health services to make health decisions. This study aimed to develop and validate a Health Literacy Environment Scale (HLES) that is suitable for Chinese culture. Methods This study was conducted in two phases. First, using the Person-Centered Care (PCC) framework as a theoretical framework, initial items were developed by using the existing health literacy environment (HLE) related measurement tools, literature review, qualitative interviews, and the researcher’s clinical experience. Second, scale development was based on two rounds of Delphi expert consultation and a pre-test conducted with 20 hospitalized patients. Using 697 hospitalized patients from three sample hospitals, the initial scale was developed after item screening and its reliability and validity were evaluated. Results The HLES comprised 30 items classified into three dimensions as follows: interpersonal (11 items), clinical (9 items), and structural (10 items) dimensions. The Cronbach’s α coefficient of the HLES was 0.960 and the intra-class correlation coefficient was 0.844. The confirmatory factor analysis verified the three-factor model after allowing for the correlation of five pairs of error terms. The goodness-of-fit indices signified a good fit for the model (χ2/df = 2.766, RMSEA = 0.069, RMR = 0.053, CFI = 0.902, IFI = 0.903, TLI = 0.893, GFI = 0.826, PNFI = 0.781, PCFI = 0.823, PGFI = 0.705). The item-content validity index ranged from 0.91 to 1.00, and the scale-content validity index was 0.90. Conclusion The HLES had good reliability and validity and provides a patient perspective tool for evaluating HLE and a new perspective for improving health literacy in China. That is, healthcare organizations make it easier for patients to access, understand, and use health information and service. Further studies about the validity and reliability of HLE should include other districts and different tiers or types of healthcare organizations.